The Use of the STAD Type (Student Teams Achievement Division) Cooperative Learning Model to Improve Students' Cultural Arts (Arts) Learning Outcomes - Amri (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
Abstract The research aims to find out whether the use of the STAD-type cooperative learning model can improve the learning outcomes of Cultural Arts (Arts) students of Class XI IPS3 SMA Negeri 1Polewali. The number of students is 35 people, which are divided into 7 working groups consisting of 5 students. Observations were carried out in two cycles, each cycle consisting of a preparation (planning), implementation of actions, observation and evaluation, reflection, and revision of actions. Data analysis was carried out descriptively, presented in tabular form, and equipped with percentage calculations. The results showed that the student's learning completeness in the first cycle was 74.28% and in the second cycle was 91.42%. Thus, there is an increase in mastery learning outcomes from cycle I to cycle II of 17.14%. It was also found that in the first cycle the number of groups who completed 14.28% increased by 42.86% to 57.14% in the second cycle. This study concludes that the use of the STAD-type cooperative learning model can improve the learning outcomes of Cultural Arts (Arts) students of class XI IPS3 SMA Negeri 1 Polewali.